Heat shock affects the Ca2+/calmodulin-dependent protein kinase II dynamic during bovine sperm capacitation and acrosome reaction - Santos, Thais de Sousa; Contrim, Isabelle Scarpini; da Silva, Daniela Franco; Assumpção, Mayra Elena Ortiz D’Avila; Paula-Lopes, Fabiola Freitas de; Feitosa, Weber Beringui (Frontiers in Cell and Developmental Biology, 2025)
BackgroundHeat shock during sperm capacitation affects the spermatozoa quality, resulting in increased early acrosome reaction and consequently decreasing their fertilizing capacity. Although the mechanisms involved in the regulation of sperm capacitation and acrosome reaction are not fully understood, it has been reported that Ca2+/calmodulin-dependent protein kinase II (CaMKII) is an important regulator of these processes. Thus, the present aimed to evaluate the effect of heat shock in the CaMKII signaling during the bovine sperm capacitation and acrosome. MethodsBovine spermatozoa were in vitro capacitated for 4 hours. The acrosome reaction was induced by exposure to heparin and calcium ionophore A23187 for 1 hour. Heat shock was applied by incubating spermatozoa at 41 °C with 7% CO2, while the control group was maintained at 38.5 °C with 5% CO2. At the end of each treatment, the localization of total CaMKII and phosphorylated CaMKII (pCaMKII), as well as acrosomal membrane integrity, were evaluated by immunofluorescence.ResultsIt was observed that CaMKII and not phosphorylated CaMKII (pCaMKII) localization at the acrosome region was affected by sperm capacitation. In contrast, the localization of both, CaMKII and its phosphorylated form was affected by the acrosome reaction (p < 0.05). The acrosome membrane integrity, as well as the pCamKII localization in bovine spermatozoa, was affected by incubation time. This effect of incubation time was stronger in heated shock sperm, although it was observed only after 2 h of incubation. Heat shock also affected the acrosomal localization of pCaMKII in the acrosomal region of spermatozoa with intact acrosome.DiscussionTaken together, the data present here show that CaMKII and pCaMKII localization is dynamic during bovine sperm capacitation and acrosome reaction and that this pattern of localization is affected by heat shock, suggesting that failure in CaMKII signaling is probably involved in the early acrosome reaction observed in heated-shock spermatozoa.